Experiências e estratégias de operadores no atendimento às necessidades de acessibilidade de passageiros com deficiências ocultas em aeroportos e viagens aéreas - Santos, Igor dos (Universidade Federal de São Carlos, 2023)
Accessibility for people with disabilities is usually based on what is regulated or prescribed. This leads to specific demands of people with disabilities, in this case passengers with hidden disabilities in air travel, being partially met because there are criteria in the planning of practical actions to promote accessibility for these individuals that are not included in the regulations. Therefore, this study has as its research theme the development of accessibility recommendations in airports for people with hidden disabilities. The objective is to understand passenger assistance processes to develop recommendations based on literature and collection of experiences from service providers at airports in Brazil. To achieve this purpose, a multi-method research approach was used. The theoretical methodological approach was based on systematic literature reviews and reviews of national and international civil aviation normative content. The empirical methodological approach was based on French ergonomics, which exposes the directions for understanding the work activity. In addition, the activity theory was also used, in the analysis of the mediating factors of the operators' activity to achieve a result: the assistance of passengers with hidden disabilities. This study is organized in the format of articles, which present the following publication proposals: (i) the state of the art with accessibility recommendations for passengers with hidden disabilities in airports, based on general transportation situations, and adapted to the typical stages of an air travel journey; (ii) review of civil aviation normative documents to develop a framework that integrates the needs of passengers and the experience of operators in a synthesis of the main procedures for assisting passengers with hidden disabilities; (iii) present a conceptual model that synthesizes the service quality indicators in airports that have a link to accessibility, in addition to a case study carried out in two airports in Brazil to exemplify the proposed theoretical model. The results obtained through theoretical contributions, including the framework and the conceptual model, translate the main strategies carried out by service providers in assisting these passengers in airports or air travel. This context of knowledge generation can be incorporated into practical contexts to assist airport and airline service providers in improving structural and service conditions in terminals.
Operators' experiences and strategies in meeting the accessibility needs of passengers with hidden disabilities at airports and air travel
Experiencias y estrategias de los operadores para satisfacer las necesidades de accesibilidad de pasajeros con discapacidad oculta en aeropuertos y viajes aéreos
Keywords: Acessibilidade; Deficiências ccultas; Ergonomia; Assistência; Viagem aérea; Aeroportos; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::PROCESSOS DE TRABALHO